El Nino or El Peso? Crisis, Poverty, and Income Distribution in the Philippines - Datt, Gaurav; Hoogeveen, Hans (World Bank, Washington, DC, 2014)
Using household survey data for 1998, the authors assess the distributional impact of the recent economic crisis in the Philippines. The results suggest that the impact of the crisis was modest, leading to a five percent reduction in average living standards, and a nine percent increase in the incidence of poverty - with larger increases indicated for the depth, and severity of poverty. The greater shock came from El Nino, rather than through the labor market. The labor market shock was progressive (reducing inequality) while El Nino shock was regressive (increasing inequality). Not all households were equally vulnerable to the crisis-induced shocks. Household and community characteristics affected the impact of the shocks. Ownership of land, made households more susceptible to the El Nino shocks, higher levels of education made households more vulnerable to wage, and employment shocks. The impact of the crisis was greater in more commercially developed communities. Occupational diversity within a household helped mitigate the adverse impact. There is some evidence of consumption smoothing by the households affected by the crisis, but the poor were less able to protect their consumption, which is a matter of policy concern.